Role of LXR alpha in regulating expression of glucose transporter 4 in adipocytes - Investigation on improvement of health of diabetic patients - Balamuralikrishnan Balasubramanian; Hak-J. Kim; Ramzi A. Mothana; Young O. Kim; Nasir A. Siddiqui (Elsevier, 2020)
Background: The insulin-responsive glucose transporter 4 (GLUT4) plays prominent role in insulin-mediated facilitated glucose uptake into most of the cell types, majorly muscle, liver and adipose tissue. Impaired expression of GLUT4 has been linked to insulin resistance and diabetes. In adipocytes, excess lipids that are generated from liver and by de novo lipogenesis utilizing blood sugar, are stored. There are various nuclear factors, co-factors and signaling mechanisms that directly and indirectly regulate glucose transporter activity in adipocytes. Molecular mechanism behind the regulation of GLUT4 in adipocytes has not elucidated well. Objective: Therefore, the present study focuses to explore the role of Liver X receptor- alpha (LXRα) on GLUT4 expression and the possible co-factors involved during in vitro adipogenesis and is assessed by modulating the activity of LXRα with specific agonist and antagonist ligands in 3T3L1 differentiated cells. Results: The results demonstrate that SR 9238 (300 nM), a strong inhibitor of LXRα, decreased the rate of adipogenesis through reduced lipid droplet formation in adipocytes without affecting the cell morphology. The FMOC-l-Leucine (FLL), a known partial ligand of PPARγ, enhanced the expression of LXRα. Thus, it can be concluded that LXRα has a significant role in adipocyte differentiation and FLL interaction promoted the transcription of LXRα, thereby promotes GLUT4 expression. The results in this study identified the role of LXRα in regulating the expression of GLUT4 through SRC1. Conclusion: The study is of much relevance in treatment of diabetes and also opens the possibility of identifying new drug molecules that target LXRα. Keywords: LXRα, Diabetes, GLUT4, PPARγ, Adipocyte, Insulin resistance